TOWARD A FRAMEWORK FOR SUSTAINABLE EXPERIENCE DESIGN EDUCATION AND AN ILLUSTRATIVE CASE OF A SERVICE DESIGN THINKING COURSE - Kim Yong Se; Kamal Rida (United Kingdom, 2025)
In sustainable experience design education, experience activities of consumers and users, design activities of student designers, and education activities of instructors should be addressed. It would be meaningful to compare various sustainable experience design education efforts considering regional and cultural context. This paper describes a framework where experience, design and education activities are systematically represented with diverse contexts also represented in a structured manner. Student design projects in a service design thinking course are illustrated where sustainability is gently introduced.
ICED23: The 24th International Conference on Engineering Design